MAIN DIRECTIONS OF DEVELOPMENT RUSSIAN OIL REFINING ENTERPRISES IN CONDITIONS OF SANCTIONS - V. Ashikhin (Publishing House of the State University of Management, 2017)
The article presents the impact of sanctions on russian financial companies, enterprises of the military-industrial complex, oil and gas industry, as well enterprises of the energy and agro-industrial sectors of the economy. The main financial indicators of the economic activity of the oil refining enterprise are considered. The estimation of the factors influencing financial stability of the enterprise is presented. In the article there is the notion of financial stability, as indicators of the reflecting financial condition of the enterprise. The ways of increasing the financial stability of enterprises under the conditions of sanctions are suggested.